Sclerosing composition

A curable composition with a (meth)acryloyl group-containing polyisobutylene polymer and paraffin wax addresses the tackiness issue, enhancing handling and assembly by improving surface tackiness and maintaining transparency.

JP7611714B2Active Publication Date: 2025-01-10KANEKA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021008379
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-22
Publication Date
2025-01-10
Estimated Expiration
2041-01-22

AI Technical Summary

Technical Problem

Curable compositions containing polyisobutylene polymers with (meth)acryloyl groups exhibit noticeable surface tackiness, making them difficult to handle, and existing methods to reduce tackiness, such as using air oxidation curable substances or paraffin wax, are either ineffective or not well-documented.

Method used

A curable composition comprising a (meth)acryloyl group-containing polyisobutylene polymer, a monomer with unsaturated groups, a radical polymerization initiator, and an organic compound with a melting point of 30°C or higher and no polymerizable functional groups, specifically paraffin wax, to improve surface tackiness.

Benefits of technology

The composition achieves improved surface tackiness, allowing for easier handling and assembly, with a steel ball rolling distance of 60 mm or more in a rolling ball tack test, and maintains transparency and physical properties suitable for various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611714000001
    Figure 0007611714000001
  • Figure 0007611714000002
    Figure 0007611714000002
  • Figure 0007611714000003
    Figure 0007611714000003
Patent Text Reader

Abstract

To provide a curable resin composition which is excellent in curability and various physical properties as an elastomer and is improved in surface tackiness.SOLUTION: The curable composition contains (A) a (meth)acryloyl group-containing polyisobutylene polymer, (B) a monomer containing an unsaturated group, (C) a radical polymerization initiator, and (D) an organic compound having a melting point of 30°C or higher and having no polymerizable functional group. The curable composition contains 0.01-300 pts.wt. of (B), 0.001-20 pts.wt. of (C), and 0.001-20 pts.wt. of (D) based on 100 pts.wt. of (A).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable composition containing a polyisobutylene polymer having a (meth)acryloyl group, and a cured product thereof. [Background technology]

[0002] 2. Description of the Related Art Polyisobutylene polymers having (meth)acryloyl groups have been known as resins suitable for use in applications such as inks, paints, adhesives, sealants, precision parts for electrical and electronic applications, and shaped objects.

[0003] This resin has an excellent balance of durability, heat resistance, weather resistance, water resistance, and gas barrier properties, and can be cured with active energy rays such as UV (ultraviolet rays) and EB (electron beam), which is known to enable energy savings, space savings, and improved productivity (Patent Documents 1 and 2).

[0004] Patent Document 3 describes that paraffin may be added to the photocurable elastomer composition, but does not disclose the effects of adding paraffin, nor has it been verified in any examples. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO2013 / 047314 publication [Patent Document 2] JP 2013-216782 A [Patent Document 3] JP 2014-148644 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, as a result of investigations by the present inventors, it was found that a curable composition containing such a resin may have a problem in that the surface may be significantly tacky (sticky), making handling difficult.

[0007] Patent Documents 1 and 2 disclose the addition of an air-oxidation-curable substance or a photocurable substance as a technique for reducing such tack (also called residual tack). However, the present inventors have found that when tung oil is used as the air-oxidation-curable substance, there is a problem that the surface of the curable composition does not cure and an uncured material remains. Furthermore, no other methods are disclosed.

[0008] Also, the addition of paraffin wax as a processing aid is described, but the effect of this substance on surface tack is not disclosed.

[0009] Patent Document 3 describes that paraffin wax may be added to the photocurable elastomer composition, but does not describe the effects of adding paraffin wax, and it was unknown what effect the substance has on the surface tackiness.

[0010] The present invention has been made in consideration of the above-mentioned problems, and provides a curable resin composition containing a polyisobutylene-based polymer having a (meth)acryloyl group, which is excellent in curability and various physical properties as an elastomer and has improved surface tack. [Means for solving the problem]

[0011] The present inventors have found that the above problems can be solved by using an organic compound having a melting point of 30° C. or higher and no polymerizable functional group in a curable composition containing a polyisobutylene polymer having a (meth)acryloyl group, and have completed the present invention. (1) A curable composition containing (A) a (meth)acryloyl group-containing polyisobutylene polymer, (B) a monomer containing an unsaturated group, (C) a radical polymerization initiator, and (D) an organic compound having a melting point of 30°C or higher and no polymerizable functional group, the curable composition containing 0.01 to 300 parts by weight of (B), 0.001 to 20 parts by weight of (C), and 0.001 to 20 parts by weight of (D) relative to 100 parts by weight of (A); (2) A curable composition, wherein the component (D) is paraffin. (3) A curable composition, wherein the component (C) is a photoradical polymerization initiator. (4) A curable composition characterized in that a (meth)acryloyl group is present at at least one or more ends of the (meth)acryloyl group polymer chain of the component (A). (5) A curable composition, wherein the (meth)acryloyl group of the component (A) is represented by general formula (1).

[0012] [ka]

[0013] (R 1 R represents a hydrogen atom or a methyl group. 2 R represents a divalent saturated hydrocarbon group having 2 to 6 carbon atoms and containing no heteroatoms. 3 ~R 6 each represents hydrogen or a monovalent hydrocarbon group or alkoxy group having 1 to 20 carbon atoms. (6) A curable composition characterized in that the (A) component has at least 0.5 (meth)acryloyl groups per molecule at the terminal of the main chain of a polyisobutylene polymer. (7) A cured product obtained by curing any one of the curable compositions described above, characterized in that in a rolling ball tack test using a 7 / 16 inch (11.1 mm) steel ball in accordance with ASTM D 3121, the cured product has a movement distance of 60 mm or more. (8) A sealing material obtained by curing the curable composition according to any one of the above. Regarding. Effect of the Invention

[0014] According to the present invention, there is provided a curable composition containing a polyisobutylene-based polymer having a (meth)acryloyl group, which is a curable resin composition that is excellent in curability and various physical properties as an elastomer and has improved surface tack. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The curable composition of the present invention is a curable composition containing (A) a (meth)acryloyl group-containing polyisobutylene polymer, (B) a monomer containing an unsaturated group, (C) a radical polymerization initiator, and (D) an organic compound having a melting point of 30°C or higher and no polymerizable functional group, characterized in that the curable composition contains 0.01 to 300 parts by weight of (B), 0.001 to 20 parts by weight of (C), and 0.001 to 20 parts by weight of (D) relative to 100 parts by weight of (A).

[0016] <(A) (Meth)acryloyl Group-Containing Polyisobutylene Polymer> As the monomer constituting the main chain of the polyisobutylene polymer of component (A), isobutylene is mainly used, but other cationically polymerizable monomers may be copolymerized within a range that does not impair the effects of the present invention.

[0017] Examples of such monomers include olefins having 4 to 12 carbon atoms, vinyl ethers, aromatic vinyl compounds, vinyl silanes, and allyl silanes. Specific examples include isoprene, amylene, 1,3-butadiene, 1-butene, 2-butene, 2-methyl-1-butene, 3-methyl-1-butene, pentene, 4-methyl-1-pentene, hexene, vinylcyclohexene, α-pinene, β-pinene, limonene, styrene, indene, α-methylstyrene, methoxystyrene, methylstyrene (any of o-, m-, or p-forms is acceptable), vinyltoluene, trimethylstyrene, chlorostyrene, dichlorostyrene, methyl vinyl ether, ethyl vinyl ether, isobutyl vinyl ether, vinyltrichlorosilane, vinyl Examples of the silane derivatives include divinylmethyldichlorosilane, vinyldimethylchlorosilane, vinyldimethylmethoxysilane, vinyltrimethylsilane, divinyldichlorosilane, divinyldimethoxysilane, divinyldimethylsilane, 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, trivinylmethylsilane, tetravinylsilane, allyltrichlorosilane, allylmethyldichlorosilane, allyldimethylchlorosilane, allyldimethylmethoxysilane, allyltrimethylsilane, diallyldichlorosilane, diallyldimethoxysilane, and diallyldimethylsilane.

[0018] Among these, isoprene, amylene, 1,3-butadiene, 1-butene, α-pinene, β-pinene, limonene, styrene, indene, α-methylstyrene, methylstyrene (including o-, m- and p-isomers), methyl vinyl ether, ethyl vinyl ether and isobutyl vinyl ether are preferred from the viewpoint of copolymerizability.

[0019] When using other monomers copolymerizable with isobutylene, in order to maintain the effects of the present invention, the content of the other monomers in the polyisobutylene polymer may be preferably 50% by weight or less, more preferably 30% by weight or less, and even more preferably 10% by weight or less.

[0020] The molecular weight of component (A) is not particularly limited, but from the viewpoints of ease of handling and physical properties of the cured product, the number average molecular weight in terms of polystyrene measured by SEC (size exclusion chromatography) is preferably 500 to 500,000, more preferably 1,000 to 200,000, and even more preferably 2,000 to 100,000.

[0021] A molecular weight of less than 500 is not preferred because it may be difficult to exhibit physical properties characteristic of polyisobutylene polymers, whereas a molecular weight of more than 500,000 is not preferred because it may be difficult to handle due to lack of flowability and processability.

[0022] The molecular weight distribution of component (A) is not particularly limited, but is preferably in the range of 1.0 to 2.0, more preferably 1.0 to 1.8, and even more preferably 1.0 to 1.6, as expressed by (weight average molecular weight Mw) / (number average molecular weight Mn), using the values ​​of weight average molecular weight Mw and number average molecular weight Mn in terms of polystyrene measured by SEC measurement.

[0023] If the molecular weight distribution value exceeds 2.0, this is not preferred since the processability, ease of handling and physical properties may be impaired.

[0024] The number of (meth)acryloyl groups in the component (A) is not particularly limited, but from the viewpoints of the physical properties of the cured product obtained, fast curing property, and productivity, it is preferable that the polyisobutylene polymer has an average of 0.5 or more, more preferably 1.0 or more, and even more preferably 1.5 or more. The number of (meth)acryloyl groups is preferably 10.0 or less, and more preferably 5.0 or less on average.

[0025] If the number of (meth)acryloyl groups per molecule is 0.5 or less on average, the tackiness may deteriorate and the physical properties of the resulting cured product may be insufficient, which is not preferred. Conversely, if the number of (meth)acryloyl groups per molecule is more than 10.0 on average, the resulting cured product may be too hard, which is not preferred.

[0026] The manner in which the (meth)acryloyl group of component (A) is bonded to the main chain of the polyisobutylene polymer is not particularly limited, but examples include an ester bond, an ether bond, an amide bond, a urethane bond, a thioether bond, a carbonate bond, a urea bond, and a bond consisting of a divalent or higher hydrocarbon group not containing a hetero atom.

[0027] Among these, ester bonds, ether bonds, amide bonds and urethane bonds are preferred from the viewpoint of ease of synthesis and availability.

[0028] The bonding position of the (meth)acryloyl group of component (A) is not particularly limited and may be bonded to any position in the main chain, but it is preferable that it is bonded to at least one or more terminals of the main chain because the physical properties of the resulting cured product as an elastomer material are favorable. Bonding to an end of the main chain maximizes the molecular weight between crosslinking points in the cured polymer network, and provides favorable physical properties such as elongation and strength.

[0029] There are no particular restrictions on the structure of the (meth)acryloyl group of the component (A), but from the standpoint of availability of raw materials and ease of production, a structure represented by the following general formula (1) is preferred.

[0030] [ka]

[0031] (R 1 R represents a hydrogen atom or a methyl group. 2 R represents a divalent saturated hydrocarbon group having 2 to 6 carbon atoms and containing no heteroatoms. 3 ~R 6 each represents hydrogen or a monovalent hydrocarbon group or alkoxy group having 1 to 20 carbon atoms. The polyisobutylene polymer preferably has at least 0.5 units per molecule at the terminal of the main chain, and more preferably has 0.8 units or more, because the physical properties of the resulting cured product as an elastomer material are favorable.

[0032] R in the above general formula (1) 1 R represents a hydrogen atom or a methyl group. 1 When R is hydrogen, it becomes an acryloyl group, and R 1 When the alkyl group is a methyl group, the alkyl group becomes a methacryloyl group.

[0033] The acryloyl group or methacryloyl group can be selected arbitrarily depending on the combination with other compounding ingredients to be compounded in the curable composition of the present invention. For example, when an acrylic acid ester monomer is added to adjust various physical properties of the curable composition of the present invention, R 1 It is preferable to select hydrogen as the alkyl group because the reactivity of each component becomes equal, resulting in a cured product having a uniform composition.

[0034] On the other hand, when adding methacrylate monomers for the purpose of improving the physical properties of the cured product, such as heat resistance, R 1 For the same reason, it is preferable to select a methyl group as

[0035] However, these combinations are arbitrary, and the above does not apply when it is preferable for the constituent components to have different reactivities in order to achieve a specific purpose. That is, R 1 Alternatively, hydrogen may be selected as R in the general formula (1) and a methacrylic monomer may be combined as the component (B). 1 A methyl group may be selected as the (B) component in combination with an acrylic monomer.

[0036] R in the above general formula (1) 2is a divalent saturated hydrocarbon group having 2 to 6 carbon atoms and containing no heteroatoms. Specific examples include, for example, -CH2CH2-, -CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2CH2-, and the like. Among these, -CH2CH2-, -CH2CH2CH2-, and -CH2CH2CH2CH2- are preferred from the viewpoints of availability of raw materials and reactivity.

[0037] R in the above general formulas (1) and (2) 3 ~R 6 are each hydrogen, a monovalent hydrocarbon group having 1 to 20 carbon atoms, or an alkoxy group. Specific examples of the monovalent hydrocarbon group having 1 to 20 carbon atoms or the alkoxy group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a 2-ethylhexyl group, a nonyl group, a decanyl group, a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, and a butoxy group.

[0038] Among these, hydrogen and a methyl group are preferred from the viewpoint of reactivity, and hydrogen is more preferred when the availability of raw materials is also taken into consideration.

[0039] The method for producing the component (A) is not particularly limited, and reference can be made to the production methods described in patent documents WO2013 / 047314, JP2013-216782A, WO2017 / 099043A, and the like by the same applicant.

[0040] Specifically, there is a method in which a polyisobutylene polymer skeleton is produced by living cationic polymerization of isobutylene in the presence of a monofunctional and / or polyfunctional polymerization initiator, in the presence of a Lewis acid catalyst such as TiCl4 and an electron donor component such as a nitrogen-containing compound, and then the polymer terminals are functionalized using a phenoxyalkyl (meth)acrylate compound or the like. These reactions are carried out at low temperatures, such as -70°C. The reason these methods are preferred is that the raw materials are easily available, the productivity is high, and they can be used industrially.

[0041] <(B) Monomer containing an unsaturated group> The component (B) is a compound that is polymerized by the radical species generated from the component (C) of the present invention, and may be either monofunctional or polyfunctional (difunctional or higher). This component is used as a reactive diluent.

[0042] Examples of such components include compounds described in patent documents WO2013 / 047314 and JP2013-216782A, all of which are filed by the same applicant.

[0043] Specific examples include linear or cyclic (meth)acrylate monomers, styrene monomers, conjugated diene monomers, acrylonitrile, N-vinylpyrrolidone, acrylamide monomers, vinyl ketone monomers, and vinyl ester monomers.

[0044] Among these, (meth)acrylate monomers having an alkyl group or alicyclic group having 5 to 30 carbon atoms are preferred, because they are compatible with the component (A) and have excellent photocuring properties.

[0045] Among these, from the viewpoints that the rubber properties of the obtained cured product are good and that the viscosity of the curable composition is easily adjusted, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate (or an isomer), nonyl (meth)acrylate (or an isomer), decyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate (or an isomer), cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and (meth)acrylate are particularly preferred.

[0043] From the viewpoint of availability, isononyl (meth)acrylate, isostearyl (meth)acrylate, dicyclopentanyl (meth)acrylate, isobornyl (meth)acrylate, 1,9-nonanediol di(meth)acrylate, and trimethylolpropane tri(meth)acrylate are more preferred.

[0046] There are no particular limitations on the number average molecular weight of component (B), but it is preferably less than 500, and more preferably less than 400.

[0047] There are no particular limitations on the amount of component (B) used, but it is preferable to use 0.01 to 300 parts by weight per 100 parts by weight of component (A).

[0048] If the amount is less than 0.01 parts by weight, the effect of improving the physical properties may be insufficient, which is not preferable, whereas if the amount exceeds 300 parts by weight, the hardness may become too high, or conversely, the mechanical properties and heat resistance may decrease, which is not preferable.

[0049] The above component (B) may be used alone or in combination of two or more kinds.

[0050] <(C) Radical Polymerization Initiator> The component (C) of the present invention is a compound that generates radical species by an external stimulus such as light, heat, etc. There are no particular limitations on such a compound, but known photoradical polymerization initiators and thermal radical polymerization initiators can be suitably used.

[0051] The component (C) of the present invention is preferably a substance that generates active species capable of initiating polymerization of monomers such as radical species upon irradiation with active energy rays. The active energy rays referred to here include all light in the broad sense, such as radiation such as α-rays and β-rays, electromagnetic waves such as γ-rays and X-rays, electron beams (EB), ultraviolet rays with wavelengths of 100 to 400 nm, and visible light with wavelengths of 400 to 800 nm, and are preferably ultraviolet rays.

[0052] The component (C) is not particularly limited, and those described in WO2013 / 047314 and JP2013-216782A by the same applicant can be suitably used.

[0053] Among these, compounds having a hydroxyl group and a phenyl ketone structure, compounds having a benzophenone structure, and compounds having an acylphosphine oxide structure are preferred, and specifically, benzophenone, 3-methoxybenzophenone, 4-methylbenzophenone, 4,4'-bis(diethylamino)benzophenone, 4-chlorobenzophenone, 4,4'-dimethoxybenzophenone, 4-chloro-4'-benzyl benzophenone, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide are preferred.

[0054] Among these, benzophenone, 4,4'-bis(diethylamino)benzophenone, 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one are particularly preferred because of their good curing properties and storage stability.

[0055] These initiators may be used alone, or may be used in combination of two or more compounds selected from these groups.Furthermore, the above-mentioned compounds may be combined with other compounds.Specific examples include combinations with amines such as diethanolmethylamine, dimethylethanolamine, and triethanolamine, further combinations with iodonium salts such as diphenyliodonium chloride, and combinations with dyes such as methylene blue and amines.

[0056] When the photoradical polymerization initiator is used, a polymerization inhibitor such as hydroquinone, hydroquinone monomethyl ether, benzoquinone, p-tert-butylcatechol, etc. can be added as necessary. By allowing these to coexist, it is expected that the effect of preventing unintended curing of the curable composition and making it easier to handle can be expected.

[0057] The amount of the photoradical initiator is not particularly limited, and is preferably 0.001 to 20 parts by weight per 100 parts by weight of component (A). If it is less than 0.001 part by weight, sufficient curing properties may not be obtained, which is not preferable. On the other hand, if it exceeds 20 parts by weight, the light may not reach deep inside, which may cause an uncured layer to form on the bottom of the cured product, or the heat resistance of the cured product may decrease, which is not preferable.

[0058] The above-mentioned photoradical initiators may be used alone or in combination of two or more.

[0059] In addition, in cases where the composition can be heated during curing, a compound that generates radical species by heat (also called a thermal polymerization initiator), such as an azo initiator, peroxide, persulfuric acid, or redox initiator, may be used in combination as component (C).

[0060] Preferred thermal polymerization initiators are selected from the group consisting of azo initiators and peroxide initiators, and specific examples thereof include 2,2'-azobis(isobutyronitrile), 2,2'-azobis-2-methylbutyronitrile, t-butyl peroxypivalate, di(4-t-butylcyclohexyl)peroxydicarbonate, t-butylperoxyisopropyl monocarbonate, dicumyl peroxide, benzoyl peroxide, and mixtures thereof.

[0061] There are no particular limitations on the amount of the thermal polymerization initiator used, but it is sufficient to use 0.001 to 20 parts by weight per 100 parts by weight of the component (A).

[0062] <(D) An organic compound having a melting point of 30°C or higher and having no polymerizable functional group> The component (D) of the present invention is a compound that has the effect of improving the surface tackiness of the composition of the present invention after it is cured.

[0063] This effect is presumed to be achieved by the migration of component (D) from the inside of the composition to the vicinity of the surface (also called bleed-out). In this respect, if the compatibility with the main component of the curable composition (component (A) of the present invention) is good, the component (D) tends to remain inside, so it is considered that the tack improvement effect is difficult to obtain. Conversely, if the compatibility with the main component is poor, it is expected that the component (D) will be easily pushed out of the polymer network generated by the curing reaction, so the component (D) will easily migrate from the inside of the cured product to the surface, and as a result, it is assumed that the tack improvement effect is easily obtained.

[0064] Based on this mechanism, it would seem preferable that the components (A) and (D) of the present invention have opposite polarities. However, as a result of extensive research, the present inventors have discovered the unexpected effect that a tack improving effect can be obtained even when a hydrocarbon-based compound with similarly low polarity is added to a polyisobutylene-based polymer, which is a low-polarity polymer, and have thus completed the present invention.

[0065] The component (D) of the present invention is an organic compound having a melting point of 30° C. or higher. If the melting point is lower than 30° C., the effect of improving tackiness cannot be obtained. The melting point is more preferably 42° C. or higher, even more preferably 54° C. or higher, even more preferably 60° C. or higher, and even more preferably 68° C. or higher.

[0066] The component (D) of the present invention is an organic compound that does not have a polymerizable functional group such as a carbon-carbon double bond. If the component has such a polymerizable functional group, it is not preferable because it is difficult to obtain a tack improving effect. The polymerizable functional group here means a functional group active in radical polymerization, such as a (meth)acrylic group or an aromatic vinyl group. On the other hand, other functional groups that are not involved in radical polymerization, such as a hydroxy group, a carboxy group, an ester bond, an ether group, an amino group, an amide group, a urethane group, a carbonate group, a urea group, a halogen group, an aryl group, an alkoxy group, etc. may be contained.

[0067] The component (D) of the present invention is a compound other than the antioxidants described below.

[0068] From the viewpoint of improving tack, the component (D) of the present invention is preferably a hydrocarbon compound having a melting point of 30° C. or more and 300° C. or less, and from the viewpoint of availability, paraffin (also called paraffin wax) is more preferable.

[0069] Paraffin is a hydrocarbon compound, and generally refers to an aliphatic saturated hydrocarbon having 20 or more carbon atoms.

[0070] The paraffin may be a single component, but is preferably a mixture having a carbon number of 20 or more from the viewpoint of availability. On the other hand, liquid paraffin, which is liquid at room temperature, is not preferred because it has no effect of improving tack.

[0071] The amount of the (D) component used is not particularly limited, but from the viewpoint of the tackiness improving effect and economic efficiency, it is preferably 0.001 to 20 parts by weight, more preferably 0.01 to 10 parts by weight, relative to 100 parts by weight of the (A) component. If it is 0.001 part by weight or less, it is not preferable because a sufficient tackiness improving effect may not be obtained. On the other hand, if it exceeds 20 parts by weight, it is not preferable because the physical properties may decrease, such as the curable composition becoming too hard.

[0072] Although the desired effect can be obtained by adding a single component of the component (D) of the present invention, two or more components having different melting points may be used in combination.

[0073] <Other optional ingredients> The curable composition of the present invention may also contain various additives, such as a filler, a storage stabilizer, an antioxidant, an ultraviolet absorber, a plasticizer, a flame retardant, an antistatic agent, and a pigment, within a range that does not impair the effects of the present invention.

[0074] The amounts of the filler and plasticizer are not particularly limited, but are preferably 0.1 to 500 parts by weight per 100 parts by weight of component (A).The amounts of the storage stabilizer, antioxidant, UV absorber, flame retardant, antistatic agent, and pigment are not particularly limited, but are preferably 0.01 to 20 parts by weight per 100 parts by weight of component (A).

[0075] These additives are not particularly limited, but specific examples include compounds described in patent documents WO2013 / 047314 and JP2013-216782A filed by the same applicant.

[0076] In addition, the curable composition of the present invention can be used in combination with various elastomers such as (meth)acryloyl group-containing oligomers (not including the (A) and (B) components of the present invention) and styrene-based block copolymers, as long as the effects of the present invention are not impaired. The oligomers preferably do not have a polyisobutylene skeleton. These can be used to adjust various rubber properties of the cured product.

[0077] Specific examples of the (meth)acryloyl group-containing oligomer include, but are not limited to, polybutadiene skeleton (meth)acrylates, hydrogenated polybutadiene skeleton (meth)acrylates, polycarbonate skeleton (meth)acrylates, polyether skeleton (meth)acrylates, polyester skeleton (meth)acrylates, castor oil skeleton (meth)acrylates, polyisoprene skeleton (meth)acrylates, hydrogenated polyisoprene skeleton (meth)acrylates, epoxy (meth)acrylates, and (meth)acrylic group-containing acrylic polymers.

[0078] Among these, (meth)acrylates having a polybutadiene skeleton, (meth)acrylates having a hydrogenated polybutadiene skeleton, (meth)acrylates having a castor oil skeleton, (meth)acrylates having a polyisoprene skeleton, and (meth)acrylates having a hydrogenated polyisoprene skeleton are preferred because they have excellent compatibility with the components (A) and (B) of the present invention.

[0079] The oligomer refers to a compound having a structure with repeating units of a monomer in the main chain and consisting of 2 to 1,000 repeating units. There is no particular restriction on the number average molecular weight, but it is preferably 200 to 500,000, and more preferably 1,000 to 100,000.

[0080] Specific examples of various elastomers such as styrene-based block copolymers include, but are not limited to, styrene-based copolymers, such as styrene-butadiene copolymer, styrene-isoprene copolymer (SIP), styrene-butadiene copolymer (SB), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-isobutylene-styrene copolymer (SIBS), acrylonitrile-styrene copolymer (AS), and styrene-butadiene-acrylonitrile copolymer (ABS).

[0081] Among these, from the viewpoints of compatibility and rubber properties, styrene-butadiene copolymer, styrene-isoprene copolymer (SIP), styrene-butadiene copolymer (SB), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-isobutylene-styrene copolymer (SIBS), etc. are preferred.

[0082] The amount of the oligomer used is not particularly limited, but is preferably 0.1 to 1,000 parts by weight per 100 parts by weight of the component (A).

[0083] The curable composition of the present invention may contain a thiol compound in combination within a range that does not impair the effects of the present invention.

[0084] Specific examples of these thiol compounds are not particularly limited, and include, for example, decanethiol, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), trimethylolpropane tris(3-mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate), ethylene glycol bis(3-mercaptoglycolate), butanediol bis(3-mercaptoglycolate), trimethylolpropane tris(3-mercaptoglycolate), pentaerythritol tetrakis(3-mercaptoglycolate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, pentaerythritol tetrakis(3-mercaptopropionate), and tetraethylene glycol. Examples of the compound include bis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, and 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione. These compounds may be used alone or in combination of two or more.

[0085] In order to improve the photocurability of the present invention, a tertiary amine compound may be blended. The tertiary amine compound is not particularly limited, but examples thereof include trimethylamine, triethylamine, tributylamine, N,N'-diethanolamine, N,N'-dimethyl-p-toluidine, N,N'-dimethyl-aniline, N-methyl-diethanolamine, N-methyl-dimethanolamine, N,N'-dimethylamino-acetophenone, N,N'-dimethylaminobenzophenone, N,N'-diethylamino-benzophenone, and triisopropanolamine. The amount of the thiol compound used is not particularly limited, but is preferably 0.1 to 100 parts by weight relative to 100 parts by weight of the (A) component.

[0086] In addition, the curable composition of the present invention may contain an adhesive and / or adhesion imparting agent within a range that does not impair the effects of the present invention.

[0087] Specific examples of such adhesive and / or adhesion-imparting agents include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, methacryloxyoctyltrimethoxysilane, vinyltrimethoxysilane, vinyltrichlorosilane, vinyltriethoxysilane, vinyl-tris(β-methoxyethoxy)silane, γ-chloropropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. Methoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-ureidopropyltriethoxysilane, hydroxyethyl methacrylate phosphate, methacryloxyoxyethyl acid phosphate, methacryloxyoxyethyl acid phosphate monoethylamine half salt, 2-hydroxyethyl methacrylic acid phosphate, etc. Among these, hydroxyethyl methacrylate phosphate, methacryloxyoxyethyl acid phosphate, methacryloxyoxyethyl acid phosphate monoethylamine half salt, 2-hydroxyethyl methacrylic acid phosphate, etc. can be mentioned.

[0088] The content of the adhesion imparting agent is preferably 0.01 to 20 parts by weight, and more preferably 0.1 to 10 parts by weight, per 100 parts by weight of the component (A).

[0089] <Method of producing curable composition> The method for producing the curable composition of the present invention is not particularly limited. All of the ingredients may be prepared as a one-component type, or the ingredients may be separately blended in consideration of the storage stability of the composition, and then mixed before use to prepare a two-component type. The one-component type eliminates the need for mixing and kneading during application, and also eliminates the measurement errors that occur during this process, making it the most preferable form for preventing quality defects such as poor hardening.

[0090] In the case of a two-component type, each compounding component may be divided into two liquids as desired, and the two-component type may be prepared by mixing the compounding components before use. Various combinations are possible for the method of dividing into two liquids, liquid A and liquid B, taking into consideration the mixing ratio of the curable composition, storage stability, mixing method, pot life, etc. If necessary, a third component may be prepared in addition to the liquids A and B to form a three-liquid type curable composition, and further division into parts may also be adjusted as necessary.

[0091] Because component (D) is a solid at room temperature, it may be heated to 30 to 300°C to melt it and then added to component (A) or a mixture of components (A) and (B); alternatively, if component (D) melts during mixing at the temperatures described below, it may be mixed in its solid or powder form with the other components.

[0092] The method for mixing the composition of the present invention is not particularly limited, and the composition can be produced, for example, by blending the above-mentioned components, shielding them from light if necessary, and kneading them using a hand mixer, static mixer, planetary mixer, disperser, roll, kneader, single-screw extruder, twin-screw extruder, Banbury mixer, Brabender, high-shear mixer, etc. As for the temperature during kneading, typical methods include kneading at room temperature or under heating, or dissolving the components using a small amount of a suitable solvent and mixing them.

[0093] The mixing temperature is preferably from 10 to 100°C, and more preferably from 20 to 80°C.

[0094] The mixing time is preferably about 0.1 to 5 hours, and more preferably about 30 minutes to 3 hours.

[0095] <Application method> The curable composition of the present invention can be applied to an adherend by a method similar to that used for a known sealant or adhesive, such as dispensing using an automatic coater, spraying, inkjet printing, screen printing, gravure printing, dipping, spin coating, or the like.

[0096] The curable composition of the present invention is preferably liquid at 25° C. from the viewpoint of ease of handling.

[0097] The viscosity of the curable composition of the present invention is not particularly limited, but in terms of applicability to various coating methods, the viscosity at room temperature is preferably 0.0001 to 10,000 Pa sec, and more preferably 0.001 to 5,000 Pa sec in terms of ease of handling.

[0098] For applications where a low viscosity is preferred, such as spray, inkjet, and screen printing, the viscosity is preferably 0.0001 to 5,000 Pa·sec, and more preferably 0.0001 to 3,000 Pa·sec. The lower the viscosity, the easier it is to handle, and conversely, a viscosity of 5,000 Pa·sec or more is not preferred, as it may be difficult to eject the desired liquid.

[0099] On the other hand, when used for FIPG (form-in-place gasket), CIPG (cured-in-place gasket), MIPG (mold-in-place gasket), LIM (liquid injection molding), and other dispensing applications, the viscosity is preferably 0.001 to 10,000 Pa·sec, and more preferably 0.001 to 5,000 Pa·sec. If it is less than 0.001 Pa·sec, the thixotropy may be insufficient and it may not be possible to mold it into the intended shape, which is not preferable. Conversely, if it is more than 10,000 Pa·sec, it is not preferable because a high discharge speed cannot be obtained, which may reduce productivity.

[0100] When the viscosity at 25° C. is high and handling is difficult, the composition of the present invention may be heated to a desired viscosity. The temperature at that time is preferably 100° C. or lower, more preferably 80° C. or lower.

[0101] <Curing method> The light source used when irradiating the curable composition of the present invention with the above-mentioned active energy rays, for example, ultraviolet light, visible light, or the like, to cure the composition is not particularly limited, and examples of the light source that can be used include a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a black light lamp, a microwave-excited mercury lamp, a metal halide lamp, a sodium lamp, a halogen lamp, a xenon lamp, an LED, a fluorescent lamp, sunlight, an electron beam irradiation device, and a laser.

[0102] The amount of light irradiation is 1 kJ / m2, based on the characteristics of the cured product. 2 It is preferable that the concentration is equal to or higher than 10 kJ / m 2 The cumulative light intensity is 1 kJ / m 2 If the temperature is less than this, the composition may not be sufficiently cured, which is undesirable.

[0103] Furthermore, by matching the wavelength of the light emitted from each of the above light sources as closely as possible to the absorption wavelength of component (C) (and / or its maximum absorption wavelength), efficient curing can be achieved.

[0104] <Cured product> The cured product of the present invention is obtained by curing the cured resin composition of the present invention by irradiating it with active energy rays such as ultraviolet rays using the above-mentioned curing method. The cured product of the present invention may be obtained by curing the curable composition of the present invention, regardless of the curing method used.

[0105] The cured product of the present invention has a low surface tackiness, which improves the conventional problems of dust adhesion, difficulty in handling, etc. In addition, the improved tackiness makes the cured product easier to handle, which has the advantage of making it easier to assemble products and to remake them, for example.

[0106] There is no limitation on the method for quantitatively measuring the tack of the cured product of the present invention, but as an example, it can be measured by a rolling ball tack test using a 7 / 16 inch (11.1 mm) steel ball in accordance with ASTM D 3121. The moving distance of the steel ball in this test is preferably 60 mm or more, more preferably 100 mm or more, and even more preferably 150 mm or more. The turbidity of the cured product of the present invention can be kept low depending on the content of component (D). Such a cured product has improved tackiness, low turbidity (white turbidity), and a nearly transparent appearance, making it suitable for use in applications and locations where transparency is required.

[0107] The turbidity of the cured product of the present invention can be measured in accordance with JIS K 7136, and the value is preferably 100 or less, and more preferably 80 or less.

[0108] <Application> The curable composition and cured product of the present invention can be used for the following applications: Namely, they can be suitably used for applications such as electrical and electronic parts, sealing materials, coating materials, adhesives, sealing materials, and molded parts for pharmaceutical and medical products, sealing materials for electrolytic capacitors, resist materials, on-site formed gaskets, vibration-proof and vibration-damping materials, sealing materials for insulating glass, coating materials and sealing materials for electric wires, cables, and optical fibers, rollers, sheets, sealing materials, adhesives, pressure-sensitive adhesives, molded bodies, paints, inks, and foams.

[0109] The sealing agent herein includes applications such as adhesives, coating agents, casting agents, and potting agents.

[0110] In electrical and electronic applications, they can be used, for example, as materials for LEDs, various battery peripheral materials, sensors, semiconductor peripheral materials, circuit board peripheral materials, display peripheral materials such as liquid crystal displays, lighting materials, optical communication and optical circuit peripheral materials, optical recording peripheral materials, and magnetic recording materials.

[0111] As an LED material, it can be used as a molding material, encapsulant, encapsulating film, die bond material, coating material, sealing material, adhesive, pressure-sensitive adhesive, and lens material for LED elements, as well as a sealing material, adhesive, pressure-sensitive adhesive, and coating material for LED light bulbs, LED indicator lights, LED display boards, LED displays, etc.

[0112] As battery peripheral materials, they can be used for sealing materials for lithium ion batteries, sodium-sulfur batteries, sodium molten salt batteries, organic radical batteries, nickel-metal hydride batteries, nickel cadmium batteries, redox flow batteries, lithium-sulfur batteries, air batteries, electrolytic capacitors, electric double layer capacitors, lithium ion capacitors, fuel cells, solar cells, dye-sensitized solar cells, etc., back surface sealing materials, molding materials for each element, adhesives, pressure sensitive adhesives, sealing materials, sealing films, coating materials, potting materials, fillers, separators, coatings for fixing catalysts, protective films, electrode binders, refrigerant oil sealing materials, hose materials, etc.

[0113] The materials can be used as sealants, sealing films, lens materials, adhesives, pressure-sensitive adhesives, coatings, films, etc. for sensors of force, load, pressure, rotation, vibration, contact, flow rate, solar radiation, light, odor, time, temperature, humidity, wind speed, distance, position, inertia, tilt, speed, acceleration, angular velocity, hardness, distortion, sound, magnetism, current, voltage, power, electrons, radiation, infrared rays, X-rays, ultraviolet rays, liquid volume, weight, gas volume, ion volume, metal volume, color, etc.

[0114] As peripheral materials for circuit boards, they can be used as sealing materials, coating materials, potting materials for rigid or flexible wiring boards mounted with various elements such as ICs, LSIs, semiconductor chips, transistors, diodes, thyristors, capacitors, resistors, and coils, as well as molding materials, underfill materials, die bonding materials, die bonding films, adhesives, pressure sensitive adhesives, sealing materials, and sealing films for the above-mentioned elements.

[0115] As display peripheral materials, they can be used as molding materials for each element such as liquid crystal displays, plasma displays, LED displays, organic electroluminescence (EL) displays, field emission displays, electronic paper, flexible displays, 3D holograms, organic thin-film transistor displays, and head-mounted displays, as well as various filters, protective films, anti-reflection films, viewing angle correction films, polarizer protective films, optical correction films, and other films, sealing materials, adhesives, pressure-sensitive adhesives, sealing materials, sealing films, coating materials for substrates and components, potting materials, fillers, visibility improving materials, lens materials, light guide plates, prism sheets, polarizing plates, retardation plates, and liquid crystal dam materials.

[0116] As a lighting material, it can be used as a sealing material, coating material, adhesive, encapsulant, and molded part for LED lighting, organic electroluminescence (EL) lighting, and inorganic electroluminescence (EL) lighting.

[0117] As peripheral materials for optical communications and optical circuits, they can be used as molding materials, sealing materials, adhesives, pressure-sensitive adhesives, sealing materials, sealing films, coating materials, potting materials, fillers, protective films, lens materials, light guide plates, prism sheets, polarizing plates, and ferrules for various elements such as organic photorefractive elements, optical fibers, optical switches, lenses, optical waveguides, light-emitting elements, photodiodes, optical amplifiers, optoelectronic integrated circuits, optical connectors, optical couplers, optical computing elements, photoelectric conversion devices, and laser elements.

[0118] As an optical recording material, it can be used as a disc substrate material for VD (video disc), CD, CD-ROM, CD-R, CD-RW, DVD, DVD-ROM, DVD-R, DVD-RW, BD, BD-ROM, BD-R, BD-RE, MO, MD, PD (phase change disc), hologram, optical card, protective film for pickup lenses etc., sealing material, adhesive, pressure sensitive adhesive, sealing material, sealing film, coating material, vibration isolating material, and vibration damping material.

[0119] As a magnetic recording material, it can be used as a vibration-proofing material, a vibration-damping material, a sealing material, an adhesive, a pressure-sensitive adhesive, a sealing material, a coating material, a cover gasket, and a card material for hard disks, magnetic tapes, and magnetic cards such as credit cards.

[0120] Other applications include anti-fouling films for touch panels, lubricating films, molding materials for IC chips, molding materials for Peltier elements, sealing bodies for electrolytic capacitors, cable joint potting materials, potting materials for IGBTs (vehicle propulsion control devices), dicing tapes for semiconductor wafer processing, die bond agents, die bond films, underfills, anisotropic conductive adhesives, anisotropic conductive films, conductive adhesives, conductive pastes, thermally conductive adhesives, thermally conductive pastes, temporary fixing films, fixing films, and sealing films.

[0121] In automotive applications, it can be used as body parts, sealing materials for airtightness, vibration prevention materials for glass, vibration-proofing materials for vehicle body parts, especially window seal gaskets and door glass gaskets. It can be used as chassis parts, engine and suspension rubber for vibration and soundproofing, especially engine mount rubber and vibration-proof mount sealants. It can be used as engine parts, hoses for cooling, fuel supply, exhaust control, etc., gaskets for engine covers and oil pans, engine oil sealants, etc. In addition, it can be used as tire parts, bead parts, sidewall parts, shoulder parts, tread parts, resins for inner liners, and sealants for air pressure sensors and puncture sensors. It can also be used as sealants, sealing materials, gaskets, coating materials, molded parts, adhesives, and pressure sensitive adhesives for various electronic and control parts. It can also be used as a coating material for copper and aluminum wire harnesses and a sealant for connectors. In addition, the material can be used in lamps, batteries, windshield washer fluid units, air conditioner units, coolant units, brake oil units, electrical components, various interior and exterior parts, sealing materials for oil filters, adhesives, pressure sensitive adhesives, gaskets, O-rings, packing, molded parts such as belts, igniter HICs or potting materials for automotive hybrid ICs, etc.

[0122] In industrial applications, the composition can be used for resist applications such as permanent resist applications, solder resist applications, dry film resist applications, and electrodeposition resist applications.

[0123] It can be used in information and electrical equipment such as mobile phones, media players, tablet devices, smartphones, portable game consoles, computers, printers, scanners, projectors, inkjet tanks, etc., as sealing materials, sealing materials, adhesives, pressure-sensitive adhesives, packing, O-rings, belts, vibration-proofing materials, vibration-damping materials and soundproofing materials.

[0124] In the home appliance field, the material can be used as a sealing material, adhesive, pressure-sensitive adhesive, packing, O-ring, belt, vibration-proofing material, vibration-damping material, soundproofing material, etc. in various electrical products such as televisions, various recorders such as Blu-ray recorders and HDD recorders, projectors, game consoles, digital cameras, home video cameras, antennas, speakers, electronic dictionaries, IC recorders, FAX machines, copy machines, telephones, door phones, rice cookers, microwave ovens, oven ranges, refrigerators, dishwashers, dish dryers, IH cooking heaters, hot plates, vacuum cleaners, washing machines, chargers, sewing machines, irons, dryers, electric bicycles, air purifiers, water purifiers, electric toothbrushes, lighting equipment, air conditioners, outdoor units of air conditioners, dehumidifiers, and humidifiers.

[0125] As a molded product, it can be used for packing, O-rings, belts, tubes, hoses, valves, sheets, etc.

[0126] It can also be used as various adhesives such as reactive hot melt agents for wiring connectors, reactive hot melt adhesives, OCA (optical transparent adhesives), elastic adhesives, contact adhesives, anaerobic adhesives, UV-curable adhesives, electron beam-curable adhesives, and adhesives for touch panels and touch sensors. It can also be used as a modification of butyl-based adhesives, and as various adhesives such as masking tape, pipe corrosion prevention tape, construction waterproof tape, electrical self-adhesive tape, removable adhesive, and electric wire adhesive tape.

[0127] It can be used for a variety of coating applications, such as covering materials or repair materials for electric wires and cables, insulating seal materials for wiring connections, lining materials for gas pipes, water pipes, etc., coating materials for inorganic fillers and organic fillers, and release materials for epoxy molding in molds.

[0128] The sheet can be used as a variety of sheets, such as a heat conductive sheet, a heat dissipation sheet, an electromagnetic wave absorbing sheet, a conductive sheet, a waterproof sheet, a protective sheet for automobiles, and an impact absorbing sheet for panels.

[0129] Other applications include shock absorbing gel, shock absorbing materials for beds and shoes, intermediate layers for laminated glass, elastic paints, paints such as water-based emulsions, prepregs, various rollers for office equipment and transport, cap liners, ink repellents, inks, sealing materials for various refrigerants, sealing materials and gaskets for industrial cans and food cans, foam gaskets, and primary and secondary seals for double-insulated glass.

[0130] In medical applications, it can be used for transdermal absorption preparations and adhesives for patches, pharmaceutical and medical sealing materials, medical adhesives, medical rubber stoppers, impression materials, dental filling materials, syringe gaskets, rubber stoppers for reduced pressure blood vessels, O-rings and flat gaskets for artificial dialysis machines, packaging materials for pharmaceuticals and medical instruments, caps, cap liners, caps for vacuum blood collection tubes, sealing materials and adhesives for catheters, and sealing materials and adhesives for implantable medical devices, etc.

[0131] As vibration-damping and anti-vibration materials, they are used in electrical and electronic equipment such as stepping motors, magnetic disks, hard disks, dishwashers, dryers, washing machines, fan heaters, sewing machines, vending machines, speaker frames, BS antennas, and vibration-damping materials for VTR covers; architectural applications such as roofs, floors, shutters, curtain rails, floors, ducts, deck plates, curtain walls, stairs, doors, vibration-isolators, vibration-damping materials for structural materials, viscoelastic dampers, and earthquake-resistant mats; marine applications such as vibration-damping materials for engine rooms and measurement rooms; engines (oil pans, front covers, rocker covers), and car bodies (dashes, floors, doors, roofs, panels, and wheel houses). These materials can be used in automotive applications such as vibration-damping materials for transmissions, parking brake covers, and seat backs; camera and office equipment applications such as vibration-damping materials for TV cameras, copiers, computers, printers, cash registers, and cabinets; industrial machinery applications such as vibration-damping materials for chutes, elevators, escalators, conveyors, tractors, bulldozers, generators, compressors, containers, hoppers, soundproofing boxes, and motor covers for lawnmowers; railway applications such as railway car roofs, side panels, doors, underfloors, various auxiliary equipment covers, and vibration-damping materials for bridges; vibration-damping materials for precision vibration isolation devices for semiconductors, etc.; and as soundproofing vibration-damping materials that can handle low-frequency and high-frequency sounds near the threshold of audible range.

[0132] The curable composition of the present invention or a cured product thereof is an elastic body having excellent low gas permeability, low moisture permeability, heat resistance, acid resistance, flexibility and low tackiness, and can therefore be suitably used in applications such as fuel cells, solar cells, dye-sensitized solar cells, lithium ion batteries, electrolytic capacitors, liquid crystal displays, organic EL displays, electronic paper, LEDs, hard disk drives, photodiodes, optical communications / circuits, electric wires / cables / optical fibers, optical isolators, laminates such as IC cards, sensors, substrates, pharmaceutical / medical instruments / devices, etc.

[0133] Furthermore, the cured oil composition of the present invention has the characteristic of being rapidly cured by irradiation with active energy rays such as ultraviolet rays, and therefore can be more suitably used in applications requiring high productivity, such as fuel cells, lithium ion batteries, electrolytic capacitors, liquid crystal displays, organic EL displays, electronic paper, LEDs, and hard disk drives. EXAMPLES

[0134] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited thereto.

[0135] (molecular weight measurement) The "weight average molecular weight Mw," "number average molecular weight Mn," and "molecular weight distribution (ratio of weight average molecular weight to number average molecular weight (Mw / Mn))" were calculated using size exclusion chromatography (SEC) in terms of standard polystyrene.

[0136] The measurement was performed using a Waters GPC system as the measuring device, chloroform as the mobile phase, and a sample solution with a polymer concentration of 4 mg / ml at a column temperature of 35° C. The column (stationary phase) used was one packed with polystyrene cross-linked gel (Shodex GPC K-804 and K-802.5; both manufactured by Showa Denko).

[0137] (viscosity) Measurements were performed using a Toki Sangyo cone-plate type viscometer TVE-25H.

[0138] (Turbidity) The turbidity of the cured product of the curable composition of the present invention was measured by an integrating sphere photoelectric photometry method (JIS K 7136) using a haze meter HZ-V3 manufactured by Suga Test Instruments.

[0139] (Tensile properties) The curable composition was applied to a polyethylene sheet to a thickness of 0.5 mm, and irradiated with UV light (irradiation conditions: illuminance 500 mW / cm) using a UV irradiation device (manufactured by Fusion UV Systems Japan, model: LH6). 2 , light intensity 5,000mJ / cm 2 ) to obtain each sheet-like cured product.

[0140] A No. 7 dumbbell-shaped sample piece was punched out from the sheet in accordance with JIS K 6251. A tensile test was carried out at a tensile speed of 200 mm / min to evaluate the modulus, tensile strength, and elongation at break.

[0141] (hardness) In accordance with JIS K 6253, three test pieces were cured to a thickness of 2 mm and stacked together and measured using a Type A durometer.

[0142] (Surface tackiness) A rolling ball tack test was conducted using a 7 / 16 inch (11.1 mm) steel ball in accordance with ASTM D 3121 on a cured product measuring 50 mm wide, 400 mm long and 0.5 mm thick to evaluate tackiness. If the cured product has little tack and is in good condition, the steel ball can roll a long distance on the sheet-like cured product. Conversely, if the tack is very poor, the steel ball can only roll a short distance.

[0143] (Production Example 1) Synthesis of (meth)acryloyl group-containing polyisobutylene polymer (A-1) After replacing the inside of a 1L separable flask with nitrogen, 30mL of n-hexane (dried over molecular sieves) and 350mL of butyl chloride (dried over molecular sieves) were added and cooled to -70°C while stirring under a nitrogen atmosphere. Then, 150mL of isobutylene, 1.76g of p-dicumyl chloride and 0.29g of 2,6-lutidine were added. After the reaction mixture was cooled to -70°C, 0.84mL of titanium tetrachloride was added.

[0144] After the polymerization started, the residual isobutylene concentration was measured by gas chromatography, and the polymerization of isobutylene was terminated when 99.9% or more of the isobutylene added was consumed. Next, 3.70 mL of phenoxybutyl acrylate and 5.00 mL of titanium tetrachloride were added, and stirring was continued for another 3 hours at -70 to -80°C.

[0145] After the reaction was completed, the catalyst was deactivated by pouring the reaction mixture into a large amount of methanol. The solvent, which was mainly composed of methanol, butyl chloride, and hexane, was removed to obtain a viscous product. This product was dissolved in 650 g of butyl chloride, and 10 g of powdered activated carbon (manufactured by Futamura Chemical Co., Ltd., product name "Taiko A") was added and stirred at room temperature overnight. The activated carbon was filtered, and 0.0160 g of 4-methoxyphenol was added to the obtained filtrate, and the solvent was distilled off under reduced pressure to obtain an acryloyl group-containing polyisobutylene polymer (A-1). The number average molecular weight Mn (polystyrene equivalent) of A-1 was 12,600, the molecular weight distribution Mw / Mn was 1.20, and the number of acryloyl groups per molecule was 1.85.

[0146] (Production Example 2) Preparation of polymerization initiator (C) 20 parts by weight of DAROCURE 1173 (manufactured by Ciba Japan, 2-hydroxy-2-methyl-1-phenyl-propan-1-one) and 10 parts by weight of IRGACURE 819 (manufactured by Ciba Japan, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide) were weighed out and mixed well with a spatula for 5 minutes to prepare a photopolymerization initiator mixture (C).

[0147] [Table 1]

[0148] Comparative Example 1 The (meth)acryloyl group-containing polyisobutylene polymer (A-1), isononyl acrylate, a photopolymerization initiator composition, and AO-50 were mixed at room temperature in the ratio shown in Table 1 to obtain a curable composition. This curable composition was applied to a polyethylene sheet to a thickness of 0.5 mm and 2 mm, and irradiated with UV light (irradiation conditions: illuminance 500 mW / cm) using a UV irradiation device (manufactured by Fusion UV Systems Japan, model: LH6). 2 , light intensity 5,000mJ / cm 2 The physical properties of the cured products are shown in Table 1.

[0149] (Comparative Examples 2 to 5) In order to investigate the effects of the air-oxidation curing substances described in Patent Documents 1 and 2, curable compositions were obtained in the same manner as in Comparative Example 1, except that tung oil was added in the proportions shown in Table 1. Next, UV irradiation was performed to obtain cured products in the same manner as in Comparative Example 1, but none of the compositions cured, and therefore various physical properties of the cured products could not be measured.

[0150] As described above, even when the conventional techniques are combined, it is sometimes difficult to improve the surface tackiness, which is the object of the present invention.

[0151] (Comparative Examples 6 to 9) Next, the tack-improving effect of stearyl acrylate, which has a melting point of 30° C., was investigated. Curable compositions and cured products thereof were obtained in the same manner as in Comparative Example 1, except that stearyl acrylate was added in the proportions shown in Table 1. Various physical properties of the cured products were as shown in Table 1.

[0152] The tackiness of Comparative Examples 6 to 9 was 35 to 49 mm, which is equivalent to or worse than that of Comparative Example 1. Therefore, it is understood that even if the melting point is 30° C. or higher, in the case of an organic compound having a polymerizable functional group, the effect of improving tackiness cannot be obtained.

[0153] (Comparative Examples 10 to 13) Next, the effect of liquid paraffin in improving tackiness was investigated. Curable compositions and cured products thereof were obtained in the same manner as in Comparative Example 1, except that liquid paraffin was added in the proportions shown in Table 1. The physical properties of the cured products were as shown in Table 1.

[0154] The tackiness of Comparative Examples 10 to 13 was 32 to 48 mm, which is equivalent to or worse than that of Comparative Example 1. This shows that even if the compound is a hydrocarbon compound, the compound that is liquid at room temperature cannot improve the tackiness.

[0155] [Table 2]

[0156] (Examples 1 to 5) Next, the tack-improving effect of stearic acid (melting point 70°C) as component (D) of the present invention was examined. Curable compositions and cured products thereof were obtained in the same manner as in Comparative Example 1, except that stearic acid was added in the proportions shown in Table 1. Various physical properties of the cured products were as shown in Table 2.

[0157] The tackiness of Example 1 was 115 mm, which is lower than that of Comparative Example 1, and shows an improvement effect. In Examples 2 to 5, the steel ball moved 200 mm or more, which shows that the tackiness was further improved.

[0158] (Examples 6 to 14) Next, the tack-improving effect of paraffin waxes having different melting points as component (D) of the present invention was examined. In Examples 6 to 9, paraffin having a melting point of 42 to 44°C was used, and in Examples 10 to 14, paraffin having a melting point of 54 to 56°C was used, in the proportions shown in Table 2. Curable compositions and cured products thereof were obtained in the same manner as in Comparative Example 1, except that paraffin having a melting point of 42 to 44°C was used in Examples 6 to 9, and paraffin having a melting point of 54 to 56°C in Examples 10 to 14, were used in the proportions shown in Table 2. The physical properties of the cured products were as shown in Table 2.

[0159] In all the examples, the tackiness is lower than that in Comparative Example 1, and it is clear that there is an improvement effect.

[0160] [Table 3]

[0161] (Examples 15 to 26) Next, curable compositions and cured products thereof were obtained in the same manner as in Comparative Example 1, except that, as the component (D) of the present invention, paraffin having a melting point of 60 to 62°C was added in Examples 15 to 21, and paraffin having a melting point of 68 to 70°C was added in Examples 22 to 26, in the proportions shown in Table 3. The physical properties of the cured products were as shown in Table 3.

[0162] In all the examples, the tackiness is lower than that in Comparative Example 1, and it is clear that there is an improvement effect.

[0163] (Examples 27 to 31) Next, the tack-improving effect of dotriacontane, which has a clear structure as a long-chain alkane, as the component (D) of the present invention was examined. Curable compositions and cured products thereof were obtained in the same manner as in Comparative Example 1, except that dotriacontane was added in the proportions shown in Table 3. Various physical properties of the cured products were as shown in Table 3.

[0164] In all the examples, the tackiness is lower than that in Comparative Example 1, and it is clear that there is an improvement effect.

[0165] [Table 4]

[0166] Next, further investigations were carried out by changing various raw materials.

[0167] (Examples 32 to 36) Further investigation was carried out by changing the raw materials as shown in the formulation table in Table 4. In Example 32, 20 parts by weight of dicyclopentanyl acrylate was used, in Example 33, 50 parts by weight of dicyclopentanyl acrylate was used, in Example 34, 50 parts by weight of dicyclopentanyl methacrylate was used, in Example 35, 100 parts by weight of dicyclopentanyl methacrylate was used, in Example 36, 50 parts by weight of dicyclopentanyl methacrylate was used, and in addition, 0.3 parts by weight of Irgacure 184 was used as a photopolymerization initiator component. Except for this, a curable composition and a cured product thereof were obtained in the same manner as in Example 11. Various physical properties of the cured product were as shown in Table 4.

[0168] In all cases, the tackiness is reduced, demonstrating the effect of improvement.

[0169] (Production Example 2) Synthesis of (meth)acryloyl group-containing polyisobutylene polymer (A-2) After replacing the inside of a 2L separable flask with nitrogen, 100mL of n-hexane (dried over molecular sieves) and 1150mL of butyl chloride (dried over molecular sieves) were added and cooled to -70°C while stirring under a nitrogen atmosphere. Then, 280mL of isobutylene, 8.10g of p-dicumyl chloride and 1.13g of 2,6-lutidine were added. After the reaction mixture was cooled to -70°C, 2.70mL of titanium tetrachloride was added.

[0170] After the polymerization started, the residual isobutylene concentration was measured by gas chromatography, and the polymerization of isobutylene was terminated when 99.9% or more of the isobutylene added was consumed. Next, 16.9 ml of phenoxybutyl acrylate and 23 ml of titanium tetrachloride were added, and stirring was continued for another 3 hours at -70 to -80°C.

[0171] After the reaction was completed, the catalyst was deactivated by pouring the reaction mixture into a large amount of methanol. The solvent, which was mainly composed of methanol, butyl chloride, and hexane, was removed to obtain a viscous product. This product was dissolved in 1300 g of butyl chloride, and 20 g of powdered activated carbon (manufactured by Futamura Chemical Co., Ltd., product name "Taiko A") was added and stirred at room temperature overnight. The activated carbon was filtered, and 0.0190 g of 4-methoxyphenol was added to the obtained filtrate, and the solvent was distilled off under reduced pressure to obtain an acryloyl group-containing polyisobutylene polymer (A-2). The number average molecular weight Mn (polystyrene equivalent) of A-1 was 6,711, the molecular weight distribution Mw / Mn was 1.35, and the number of acryloyl groups per molecule was 1.83.

[0172] (Production Example 3) Synthesis of (meth)acryloyl group-containing polyisobutylene polymer (A-3) After replacing the inside of a 2L separable flask with nitrogen, 90mL of n-hexane (dried over molecular sieves) and 1100mL of butyl chloride (dried over molecular sieves) were added and cooled to -70°C while stirring under a nitrogen atmosphere. Then, 450mL of isobutylene, 2.60g of p-dicumyl chloride and 0.844g of 2,6-lutidine were added. After the reaction mixture was cooled to -70°C, 3.20mL of titanium tetrachloride was added.

[0173] After the polymerization started, the residual isobutylene concentration was measured by gas chromatography, and the polymerization of isobutylene was terminated when 99.9% or more of the isobutylene added was consumed. Next, 5.90 mL of phenoxybutyl acrylate and 10.0 mL of titanium tetrachloride were added, and stirring was continued for another 3 hours at -70 to -80°C.

[0174] After the reaction was completed, the catalyst was deactivated by pouring the reaction mixture into a large amount of methanol. The solvent, which was mainly composed of methanol, butyl chloride, and hexane, was removed to obtain a viscous product. This product was dissolved in 2000 g of butyl chloride, and 20 g of powdered activated carbon (manufactured by Futamura Chemical Co., Ltd., product name "Taiko A") was added and stirred at room temperature overnight. The activated carbon was filtered, and 0.0282 g of 4-methoxyphenol was added to the obtained filtrate, and the solvent was distilled off under reduced pressure to obtain an acryloyl group-containing polyisobutylene polymer (A-3). The number average molecular weight Mn (polystyrene equivalent) of A-3 was 24,941, the molecular weight distribution Mw / Mn was 1.22, and the number of acryloyl groups per molecule was 1.85.

[0175] (Examples 37 to 38) In Example 37, a curable composition and a cured product thereof were obtained in the same manner as in Example 11, except that the (meth)acryloyl group-containing polyisobutylene polymer (A-2) was used as the component (A). Various physical properties of the cured product were as shown in Table 4.

[0176] In Example 38, a curable composition and a cured product thereof were obtained in the same manner as in Example 11, except that the (meth)acryloyl group-containing polyisobutylene polymer (A-3) was used as the component (A). Various physical properties of the cured product were as shown in Table 4.

[0177] In all cases, the tackiness is reduced, demonstrating the effect of improvement.

Claims

1. A curable composition containing (A) a (meth)acryloyl group-containing polyisobutylene polymer, (B) a monomer containing an unsaturated group, (C) a radical polymerization initiator, and (D) an organic compound having a melting point of 30°C or higher and no polymerizable functional group, the composition containing (B) in an amount of 0.01 to 300 parts by weight, (C) in an amount of 0.001 to 20 parts by weight, and (D) in an amount of 0.001 to 20 parts by weight per 100 parts by weight of (A), A curable composition, wherein the component (D) is paraffin.

2. The curable composition according to claim 1 , wherein the component (C) is a photoradical polymerization initiator.

3. 3. The curable composition according to claim 1, wherein the component (A) has a (meth)acryloyl group at least on one or more ends of a (meth)acryloyl group polymer chain.

4. The curable composition according to any one of claims 1 to 3, characterized in that the (meth)acryloyl group of the component (A) is represented by general formula (1). 【Chemistry 1】 (R1 represents hydrogen or a methyl group. R2 represents a divalent saturated hydrocarbon group having 2 to 6 carbon atoms and having no heteroatoms. R3 to R6 each represent hydrogen or a monovalent hydrocarbon group or alkoxy group having 1 to 20 carbon atoms.)

5. The curable composition according to any one of claims 1 to 4, characterized in that the (A) component has at least 0.5 (meth)acryloyl groups per molecule at the terminal of the main chain of the polyisobutylene polymer.

6. A cured product obtained by curing the curable composition according to any one of claims 1 to 5, characterized in that in a rolling ball tack test using a 7 / 16 inch (11.1 mm) steel ball in accordance with ASTM D 3121, the cured product exhibits a movement distance of 60 mm or more.

7. A sealing material obtained by curing the curable composition according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Curable composition and usage of the same

    JP2013216782A

  • Photocurable elastomer composition, sealing material, and device

    JP2014148644A

  • (METH)acryloyl-terminated polyisobutylene polymer, method for producing same, and active energy ray-curable composition

    WO2013047314A1